2014
DOI: 10.1111/cch.12176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a food supplementation and psychosocial stimulation trial for severely malnourished children on the level of maternal depressive symptoms in Bangladesh

Abstract: The study did not show a significant effect of the intervention on the level of maternal depressive symptoms. Interventions with higher intensity and/or of longer duration focusing directly on maternal psychosocial functioning are probably needed to reduce maternal depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 56 publications
3
10
2
Order By: Relevance
“…The RCF&P group did not differ from the CF group in the total HOME score, despite receiving detailed responsive feeding and play stimulation intervention content. Our results contrast with a number of studies in which large effects were reported for mother–child interaction and the caregiving environment when responsive care and stimulation was focal to the intervention (Nahar et al, 2014; Orri, Côté, Tremblay, & Doyle, 2019; Tessier et al, 2009; Yousafzai et al, 2015). We, however, report significant difference on two subscales of the HOME scale: ‘Opportunities for Daily Stimulation’ and ‘Caregiver Promotes Child Development’ in the RCF&P group, compared with the C and CF groups from 9 to 15 months.…”
Section: Discussioncontrasting
confidence: 99%
“…The RCF&P group did not differ from the CF group in the total HOME score, despite receiving detailed responsive feeding and play stimulation intervention content. Our results contrast with a number of studies in which large effects were reported for mother–child interaction and the caregiving environment when responsive care and stimulation was focal to the intervention (Nahar et al, 2014; Orri, Côté, Tremblay, & Doyle, 2019; Tessier et al, 2009; Yousafzai et al, 2015). We, however, report significant difference on two subscales of the HOME scale: ‘Opportunities for Daily Stimulation’ and ‘Caregiver Promotes Child Development’ in the RCF&P group, compared with the C and CF groups from 9 to 15 months.…”
Section: Discussioncontrasting
confidence: 99%
“…Higher scores indicate a higher frequency of depressive symptoms. 22 Anxiety was assessed during lockdown only, and was measured using the Generalised Anxiety Disorder (GAD-7) tool, 23 which has been previously successfully deployed in Bangladesh. 24 The tool assessed the frequency of seven symptoms of anxiety over the past 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…27 Six programs were delivered only in individualized sessions, 17-19, 25, 28, 30-32 2 were delivered only in group sessions, 27,33 and 5 involved both group and individualized sessions. 14-16, 26, 29 Six programs were delivered by government health workers, 14,16,19,25,27,28,30,31 6 were delivered by trained community members, 15,17,18,29,32,33 and 1 involved both health workers and community members. 26 The intended total duration of the interventions was on average 11.5 months (SD = 5.95), which ranged from 6 months 17, 26, 29 -31, 33 to 24 months.…”
Section: Intervention Characteristicsmentioning
confidence: 99%